Postnatal depression in Greek mothers: The impact of stressful life events, social support and marital relationship - Σταματίου, Ευτυχία; Παπαληγούρα, Ζαΐρα (Psychology: the Journal of the Hellenic Psychological Society, 2020)
ABSTRACT IS AVAILABLE IN THE PDF